2006
DOI: 10.1007/s00392-006-0361-3
|View full text |Cite
|
Sign up to set email alerts
|

Temporary transcoronary pacing by coated guidewires

Abstract: Relevant bradycardias during percutaneous coronary intervention (PCI) are a rare event, but they require immediate therapy by temporary pacing. However, transvenous pacing is associated with frequent and severe complications. Therefore, we wanted to evaluate the safety and reliability of trans-coronary pacing by means of a PCI guidewire. Coronary pacing was applied to 70 consecutive patients undergoing PCI. Pacing was performed before and after PCI in a unipolar setting using standard guidewires as a cathode a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…IC-TRVP, with or without over-the-wire balloon coverage, has been previously described in animal models too [ 7 , 8 ]. In 2022, Heinroth et al published their successful IC-TRVP experience with a double-wire technique in pig models, using a polytetrafluoroethylene-covered guidewire in the proximal segment of the vessel serving as indifferent anode, and another standard guidewire, advanced into the periphery of the same coronary artery and covered with a coronary balloon, as cathode [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IC-TRVP, with or without over-the-wire balloon coverage, has been previously described in animal models too [ 7 , 8 ]. In 2022, Heinroth et al published their successful IC-TRVP experience with a double-wire technique in pig models, using a polytetrafluoroethylene-covered guidewire in the proximal segment of the vessel serving as indifferent anode, and another standard guidewire, advanced into the periphery of the same coronary artery and covered with a coronary balloon, as cathode [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pacing was achieved in 40 different coronary tracts; each site of IC stimulation was then compared to the corresponding tributary areas at cardiac magnetic resonance and to the presence, in the same segments, of an epicardial coronary stenosis ≥50%: the evidence of a myocardial scar without any stenosis reducing the coronary lumen more than 50% had significantly different conductance parameters during IC-TRVP [ 12 ]. In 2006, Heinroth et al reported a successful LAD IC-TRVP in 90% of a total of 30 patients undergoing PCI, with low risk of transient coronary spasm [ 13 ]. Recently, Mallek et al reported a case of PCI of a right coronary artery ostial lesion in which IC-TRVP allowed precise stent positioning and implantation [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The concept of cardiac pacing using a coronary artery guide wire was first investigated in 1984 by Chatelain et al who demonstrated that short term cardiac pacing via a coronary guidewire was achievable and well tolerated in a swine model [9]. Later, Heinroth et al performed a study to determine the effect of electrical insulation of the guidewire on pacing parameters during TCP [10]. Insulation using an angioplasty balloon catheter increased the success rate of myocardial capture from 77% to 100%.…”
Section: Trans Coronary Pacingmentioning
confidence: 99%